Procrastination and demographic characteristics associated with college students - Carranza Esteban, Renzo (2013)
The voluntary or involuntary postponement responsibilities that must be delivered at a set time is also known as procrastination. This phenomenon is not new in the act of man, being that recorded many years ago. It is interesting to see that one of the weaknesses that the practical man more momentum and both the least understood. The aim of the study was to determine the level of procrastination in college students based Peruvian Union University Tarapoto. Sample: 302 subjects, both sexes between 16 and 25 years. We used a non-experimental descriptive. Instruments: Procrastination Questionnaire created by Ramirez Tello and Vasquez (2013). The psychometric properties of the instrument indicate that it is valid and reliable. The results show that 33.7% of students from the Universidad Peruana Union belongs to the female gender, on the other hand can be seen that 44% of college students are between the ages of 16 and 20 years old respectively, and those with higher levels of procrastination. Also students of the Faculty of Engineering and Architecture are those with a high level of procrastination (15.9%).